Albendazole increases serum retinol concentration in primary schoolchildren with low serum retinol - Jane Florida Kalumpiu; Yenny Djuardi; Taniawati Supali (Faculty of Medicine, Universitas Trisakti, 2015)
BackgroundSoil-transmitted helminth (STH) infection is still a health problem in Indonesia. Vitamin A deficiency (VAD) is often found together with STH. The effect of the deworming program on the vitamin A status of primary school children is unknown. The objective of this study was to evaluate the effect of albendazole on serum retinol concentrations in primary school children.MethodsAn experimental study of pre-post test design without control was carried out on 118 children from grades 3-5 at one primary school in North Jakarta, from July to September 2014. Flotac examination was used to determine STH infections and high performance liquid chromatography was performed to measure serum retinol concentration. Stool and blood samples were taken twice: before and three weeks after treatment with albendazole 400 mg single dose for three consecutive days given to all children either infected or uninfected. Paired t-test was used to analyze the data. ResultsOf the 118 children, the prevalence of STH was 71.2%. The prevalence of low retinol serum (<1.05 mmol/L) was 17 (17.2%) and of mild VAD was 2 (2.0%). Albendazole given in 3 consecutive days could not increase serum retinol concentrations (p=0.055). Serum retinol concentration significantly increased after albendazole treatment in children with low retinol serum at baseline (p=0.001). ConclusionsIn children with low serum retinol concentration, treatment with albendazole increased retinol concentration. Integrated deworming and vitamin A supplementation strategies should be evaluated in this population.